Conceptual modeling : 36th International Conference, ER 2017, Valencia, Spain, November 6-9, 2017, proceedings /: 36th International Conference, ER 2017, Valencia, Spain, November 6-9, 2017, proceedings. (2017) - Unknown
No abstract available